MATLAB® Programming : Mathematical Problem Solutions - Xue, Dingyü (De Gruyter STEM, 2020)
This book presents fundamentals in MATLAB programming, including data and statement structures, control structures, function writing and bugging in MATLAB programming, followed by the presentations of algebraic computation, transcendental function evaluations and data processing. Advanced topics such as MATLAB interfacing, object-oriented programming and graphical user interface design are also addressed.